PENGARUH DEBT TO EQUITY RATIO , NET PROFIT MARGIN DAN EARNING PER SHARE TERHADAP HARGA SAHAM PT MANDOM INDONESIA Tbk - Istiqomah; Herry Winarto (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2017)
In investing, investors should be able to determine what investment goals will be done. The investment decision in question is the decision to buy, sell, or retain ownership of shares. This study aims to analyze the effect simultaneously between Debt to Equity Ratio (DER), Net Profit Margin (NPM) and Earning Per Share (EPS) on Stock Price, analyze partially influence between Debt to Equity Ratio (DER) to Stock Price and Analyze the partial influence between Net Profit Margin (NPM) on Stock Price and to analyze the partial influence between Earning Per Share (EPS) on Stock Price at PT Mandom Indonesia Tbk in Indonesia Stock Exchange. The analytical method used multiple linear regression analysis with the help of SPSS version 20. The result of research shows that the relationship between Debt to Equity Ratio (DER), Net Profit Margin (NPM) and Earning Per Share (EPS) to stock price is very strong and positive, partially closeness relationship between Debt to Equity Ratio (DER) to the stock price is very strong and positive. Partially it can be seen that the closeness of relationship between Net Profit Margin (NPM) to stock price is low and positive, and partially closeness relationship between Earning Per Share (EPS) The stock is moderate and positive.